Symbols for the Ancestors: A Study of Petilasan Pewayangan Myths in the Rahtawu of Muria Mountains, Central Java - Tohar, Ahsan (Jurnal Sosiologi Agama, 2013)
This study examines cultural and religious phenomena ofpetilasanpewayangan myths inthe mountain of Rahtawu, Muria, Central Java. Petilasan is a sacred site(s) referring to an ancestor(s). This research investigatesoral tradition of pewayangan myths that are presented in the petilasan. It studies symbols of petilasanwhich are believed to contain socio-religious and cultural meanings and values. The Rahtawu villagers believe that Rahtawu myths symbolize ‘ancestral world’ (alam leluhur),the relics of the ancient Javanese culture. For outsiders however, Rahtawu myths are superstitious, irrational, and ridiculous. The aim of this study is to examine religious and cultural meanings and values actively reproduced in activities of the Rahtawu Society.